Respuestas
Respuesta dada por:
1
Resolución:
-------------------------------------------------------------------------------
1.-) ( 3 )( -6 ) = -18
2.-) ( 4 )( -6 ) = -24
Espero q te ayude!!!!!!!!!!!!!!!!!!
-------------------------------------------------------------------------------
1.-) ( 3 )( -6 ) = -18
2.-) ( 4 )( -6 ) = -24
Espero q te ayude!!!!!!!!!!!!!!!!!!
Nathychaconxd:
Hola vivan
Respuesta dada por:
6
el doble:
![2 \times ( - 6) = 12 2 \times ( - 6) = 12](https://tex.z-dn.net/?f=2+%5Ctimes+%28+-+6%29++%3D+12)
el triple:
![3 \times ( - 6) = - 18 3 \times ( - 6) = - 18](https://tex.z-dn.net/?f=3+%5Ctimes+%28+-+6%29+%3D++-+18)
el cuádruple:
![4 \times ( - 6) = - 24 4 \times ( - 6) = - 24](https://tex.z-dn.net/?f=4+%5Ctimes+%28+-+6%29+%3D++-+24)
espero haberte ayudado
el triple:
el cuádruple:
espero haberte ayudado
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años